2015
DOI: 10.1513/annalsats.201410-443ar
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Capacity for Respiratory Care in Developing Countries. Nigeria as a Case Study

Abstract: There are unmet needs for respiratory medical care in developing countries. We sought to evaluate the quality and capacity for respiratory care in low- and lower-middle-income countries, using Nigeria as a case study. We obtained details of the respiratory practice of consultants and senior residents (fellows) in respiratory medicine in Nigeria via a semistructured questionnaire administered to physician attendees at the 2013 National Congress of the Nigerian Thoracic Society. Out of 76 society-registered memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Pre- and post-operative assessment such as spirometry, diffusion capacity, and advanced imaging remains challenging in much of Africa due to cost of personnel training and equipment. [36] Plain films and computed tomography are available on site with MRI is available only at KFH. Meanwhile, most pathology and microbiology can be performed in-house or sent to an outside facility for formal interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Pre- and post-operative assessment such as spirometry, diffusion capacity, and advanced imaging remains challenging in much of Africa due to cost of personnel training and equipment. [36] Plain films and computed tomography are available on site with MRI is available only at KFH. Meanwhile, most pathology and microbiology can be performed in-house or sent to an outside facility for formal interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…erences of NHANES III [17], Crapo et al (1981) [26], Knudson et al (1983) [27] and European standards respectively [18]. Similarly, Olanrewaju (1991) showed that Nigerian school children aged 5 to 20 years have average FVC, FEV and DEP values significantly lower than their Caucasian counterparts [28] [29]. These results revealed average values for FVC and FEV calculated on the basis of the ERS-93 [10] standards, which significantly exceed (p < 0.05) the Beninese standard spirometric values.…”
Section: Comparisons Of Our Standard Values With Those Of Ers-93mentioning
confidence: 99%
“…Data from the World Bank indicate that the lowest-income countries in the world have, in general, one-tenth the number of physicians as high-income nations on a per capita basis (5). It is safe to assume that whereas in high-income countries the physician labor supply includes generalists, specialists, and subspecialists, in low-income countries the physician labor supply consists largely of generalists, many of whom have little or no post-graduate training after medical school (6).…”
mentioning
confidence: 99%